Efeitos aditivos, não aditivos, diretos e maternos em pesos corporais até três anos de idade em animais cruzados Hereford, Angus, Salers e Nelore. - Queijo, Oscar Mario Lema (2011)
The study was divided into two independent but complementary parts. The first objective was to compare crossbreeding models to for weaning weight to design crossbreeding systems and evaluate the difference that would facilitate the selection of fitting models. A total of 4003 records were used, corresponding to 39 genotypes produced by crosses between Aberdeen Angus (A/A), Salers (S/S) and Nelore (N/N) with Hereford (H/H) breeds. Data were obtained from the Facultad de Agronomía UDELAR of Uruguay between 1993 and 2002. Nine mixed models were compared, starting from the additive model and gradually incorporated non-additive effects. In all models fixed effects where contemporary group, sex and category of the cow (primiparous or multiparous), the lineal covariates age at weaning and birth weight; random effect of were sire effect and the residual. Models including additive and dominance genetics effects fit the worst and models including epistatic effects fit the best. Models that estimate average epistatic effect for weaning weight among breeds have less capacity of detecting differences than those that estimate epistatic interaction for each breed combination. The incorporation of direct and maternal epistatic interactions is necessary for designing effective crossbreeding systems. The aim of the second study was to estimate additive and non-additive genetic effects for growth of crossbred H/H, A/A, S/S and N/N from birth to three-year-old of age. Data included 67,674 weight records of 4,050 animals from the same experiments. These records correspond to 39 different genotypes, and 143 sires. Analyses were by a multiple-trait model (MAM), with traits defined from birth to 36 mo and every 3 months; and with a repeated measure model (MMR) with records from birth to 1227 days old. All available weights were used in MMR, but only 45,794 weights were used in MAM analysis. Both models consider the fixed effects of contemporary groups (754 and 1,066 for MAM to MMR), the random effect of sire and covariates for direct and maternal additive effects (gi, gm), individual and maternal heterosis (hi, hm) and individual and maternal recombination losses (ri, rm) according to the comprehensive model of Dickerson. Additionally MMR included the permanent environment random effect of the animal. For direct additive and non-additive effects there was a good fit between the estimates of MAM and MMR, but not for maternal effects, where we found discrepancies between them. A positive effect of gi was found for A/A and S/S, and a negative effect for N/ N. For all breed combinations and ages the effects of hi were positive and the effects of ri were negative. The zebu breed showed a negative gm for all ages, however A/A showed positive additive and non-additive effects for all ages. Maternal non-additive effects (hm and rm) were positive, and these effects were bigger for S/S and N/N compared to A/A. Best combinations of additive effects is achieved with British breeds, but higher values of heterosis and recombination losses are obtained with the Zebu breed. The advantage of using crossbred females in growth is maintained until three-year-old of age for British x British and British x Continental combinations. This advantage for the Zebu x British combinations is maintained but the proportions of the former are lower than the second. Maternal additive and non-additive effects have effect on growth up to thirty-six months for all breed combinations. Keywords: additive effects, beef cattle, crossbreeding, heterosis, non-additive effects